(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: The purpose of the study was to evaluate association of serum calcium concentration with preeclampsia. Method: This study was carried out in the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2016 to December 2016 including 120 antenatal patients in their second half of pregnancy. All the included patients were classified as 40 mild preeclampsia (Group A) 40 severe preeclampsia (Group B) and 40 normal pregnant women (Group C). Serum calcium was estimated in the Department of Biochemistry and correlated with preeclampsia. Result: In results the mean serum calcium concentration was found 8.2±0.2mg /dl in Group A, 7.6 ± 0.3 mg/dl in Group B and 9.0±0.5 mg/dl in Group C (p=0.001). Low serum calcium was found 53.7% and 12.5% in case and control respectively. The difference was statistically significant (p=<0.05) between case and control groups having OR=8.1 with 95% CI (2.7 - 26.5) %. Pearson’s correlation test revealed that both systolic and diastolic blood pressure had negative correlation with the serum calcium concentration (p=<0.05). Conclusion: In conclusion this study showed that low serum calcium is associated with preeclampsia and its concentration inversely proportional to the severity of preeclampsia and both systolic and diastolic blood pressure. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.379-383